c.7 - "Agnihotri, V. K. (ed.)" (New Delhi, 1995)
Collection of articles presented at the Seminar on Public Policy Analysis and Design organized by Lal Bahadur Shastri National Academy of Administration from 23 to 25 August, 1993; with special reference to India.
Keywords: Public policy